Pelatihan Pengembangan Bahan Ajar Mengintegrasikan Praktikum dan Multipelrepresentasi Kimia dalam Pembelajaran Berbasis Masalah bagi Guru Kimia Kota Padang - Suryani, Okta; Naibaho, Sriwahyuni; Aini, Faizah Qurrata; Pangestuti, Annisa Dewi (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
The Kurikulum Merdeka on Sekolah Penggerak requires teachers that able to prepare and arranging teaching materials to support the learning process with innovative learning models, one of which is the problem-based learning. To overcome these challenges a training on Preparation of Teaching Learning Materials (TLM) Integrated with Practicum and Multiple Representation Chemistry on Problem-Based Learning has been conducted for Chemistry Teachers in Padang. This activity provide experiences to the teachers about what kind of teaching materials are using on process learning and the preparation. The activity was carried out into 2 kind activities which are 1) a workshop on Preparation of Teaching Learning Materials (TLM) Integrated with Practicum and Multiple Representation Chemistry on Problem-Based Learning, 2) a practical activity to prepare teaching materials ini the form of LKPD based on multiple representation chemistry with problem-based learning. The activity was attended by 63 participants who are chemistry teachers in Padang. The results obtained through this training are 94 % of the teacher of chemistry in Padang did not know what teaching materials use in Sekolah Penggerak, and only 4% know it. However, after the training activities, 80 % of the participants understand about teaching materials and how to prepare teaching/learning materials.